Impacto de cultivos de cobertura invernales en el stock de carbono del suelo en Chaco - Rojas, Julieta Mariana; Burdyn, Belen; Casse, Maria Florencia; Czyruk, Lorena Soledad (Asociación Argentina Ciencia del Suelo (AACS), 2020)
Póster